PEMBELAJARAN JAHIT PERCA DI KELAS XI JURUSAN KRIYA KREATIF BATIK DAN TEKSTIL DI SMK N 4 PADANG - Zelfa Efry Utami; Ranelis Ranelis; Khairul Haq (Educraf : Journal Of Craft Education, Craft Design And Creative Industries, 2022)
The research entitled the patchworck sewing lessons at the XI students in the department of creative craft batik and textile of SMK N 4 Padang. The purpose of this research was to determine: (1) the causes of the low of students' ability in patchwork sewing techniques using a sewing machine. (2) How to improve students' ability to make patchwork sewing techniques using a sewing machine. This research used a descriptive qualitative approach with the subject of students from XI students in the department of creative craft batik and textile of smk n 4 padang totaling 20 people, consisting of 19 female students and 1 male student. This research used observation, interviews, literature study and documentation in collecting the data. The results of this research indicated that the causes of the low of students' ability in patchwork sewing techniques using sewing machines were the presence of students who pay less attention to the teacher when explaining theoretical and practical material, limited learning time and constraints on the sewing machine. How to improve it by doing training outside of class hours, namely making patchwork sewing techniques using a sewing machine.